Network Security Analysis Using Snort With Intrusion Detection System (IDS) Method For Computer Network Security Optimization - Muhammad Rizki Afrizal; Amri Amri; Jamilah Jamilah (Politeknik Negeri Lhokseumawe, 2025)
Information technology, particularly computer networks, enables the rapid and complex exchange of information. Proper network management is necessary to maximize the utilization of this information. However, the more extensive the network, the more difficult it is to manage. Threats to network security, such as attacks by hackers and crackers, are increasingly widespread. These attacks can disrupt normal operations and steal critical information. In response to these threats, security systems such as the Snort IDS have been developed. Snort functions to detect and prevent attacks, as well as monitor network traffic for suspicious activity. This study aims to determine the success rate of an Intrusion Detection System (IDS) in securing computer networks against various types of attacks, whether single or multiple attacks are simultaneously executed. The study used an IDS method installed on a server to monitor network traffic. Snort's success in detecting a single attack was 100%, and its success in detecting two attacks simultaneously was 100% if there were no more than two types of attacks. Based on the results of the analysis, Snort can be implemented as an intrusion detection system on the Ubuntu 22.4 Linux operating system to detect attacks in the form of port scanning, DOS, DDOS, and brute force by capturing the attacker's IP address, which produces a response and impact on the computer's CPU that exceeds capacity.